Inisiasi Pos Pelayanan Terpadu Penyakit Tidak Menular (POSBINDU PTM) di SMA Negeri 2 Ciamis - Siti Rohimah; Undang Ruhimat; Yoga Ginanjar; Rivana Ariyadi; Tika Sastraprawira (Yayasan Inspirasi El Burhani, 2022)
Introduction: Evaluation of the Posbindu PTM program has been provided by the government, and various agencies have conducted several studies, literature review evaluation of Posbindu PTM provides an overview of input, process and output evaluations, output indicators show that the average coverage of Posbindu PTM visits is still low, the conclusion is that from each indicator the evaluation still found problems in its implementation. Objective: The purpose of this community service activity is screening, education and initiation of non-communicable disease control programs through POSBINDU PTM activities in the workplace.. Method: The implementation method used in this community service activity is an assessment using the interview method, physical examination and examination of supporting non-communicable disease risk factors. The activities are carried out in 3 stages: preparation, implementation, education and initiation. Result: Most of the participants had risky behavior, namely 91% did not eat enough vegetables and fruit, 89% lacked physical activity and risk factors for non-communicable diseases that had occurred were 78% bad body mass index, and 81% had bad cholesterol levels. Conclusion: there are still many risk factors for infectious diseases that have not been detected, especially in people who are still working, the initiation of PTM in the workplace is important to implement.